Computational Modeling of Varicella Transmission Dynamics through Cellular Automata (Cell-DEVS) - Pino Romero, Neisser (2018)
In the present paper, a computational model is performed by Cellular Automata (Cell-DEVS) that describes the transmission dynamics of Varicella in a closed group of people where the disease can be spread. From the perspective of mathematical epidemiology we have the mathematical model SEIR of W.O. Kermack and A.G. McKendrick that represent the dynamics of the epidemic, in our case Varicela, where the computational simulations are performed both by the Numerical Methods and the Cellular Automata to analyze the development of the disease.